STUDY OF PETROGENESIS AND MINERALIZATION OF ULTRAMAFIC COMPLEX ROCK OF SOPURA, DISTRICT OF KOLAKA, SOUTH EAST SULAWESI - Syahrul
The Utramafic complex in Sopura area, Kolaka, Southeast Sulawesi is part of the East Sulawesi Ophiolite (ESO). The study of petrogenesis and mineralization conducted in this study used the analysis method of rocks magnetic susceptibility, petrography, and mineragraphy. The result of geological mapping and petrographic analysis, Ultramafic Complex in Sopura region is divided into three units of rocks i.e. units of Hazburgit, Lerzolit, and Gabro. The environment of ultramafic rock formation in the study area through serpentine vein analysis and phase diagram of An-Di-Fo with 15 kbar of pressure on Lerzolite showed that the magma affinity was derived from the basal of the Mid Oceanic Ridge Basalt with the overhead of the Thetyan type. The study area is included part of an incomplete/dismembered ophiolite type ophiolit which was obducted above the continents. Contact between the sequences ofiolit is in the form of fault. The result of correlation with the ophiolit in the world is equated with the ofiolit Pindos, Greece. Measurements of rocks magnetic susceptibility obtained high magnetic susceptibility values in 7.88 x 10-3 SI of the serpentized Harzburgite rock units and 9.754 x 10-3 SI of Serpentinite and increased to the west-northwest direction. It is influenced by a fairly strong degree of serpentinization. The comparison between magnetic susceptibility analysis and mineragraphy analysis showed that the direction of chromite ore distribution also increased to that direction. Chromite sediment characteristic is chromite podiform type, including class II chromite type with deformed, non-cumulate chromite features, spreading disseminated to massive with strong deformation features, original rocks of Harzburgite.